Atomic Robo. Volume one, Atomic Robo and the Fighting Scientists of Tesladyne - Clevinger, Brian, 1978-; Wegener, Scott (Calgary, Alta., Canada : Red 5 Comics, 2008)
Collects no. 1-6 of "Atomic Robo" comics in which Atomic Robo, a robot with automatic intelligence built by Nikola Tesla in 1923, grows in stature with the U.S. military and as founder of Tesladyne, a think tank that explores the fringes of scientific inquiry.
Collects: Atomic Robo #1-6.
Adult
Keywords: Robots -- Comic books, strips, etc. -- Fiction; Scientists -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels; Robots -- Comic books, strips, etc. -- Fiction; Science fiction graphic novels; Scientists -- Comic books, strips, etc. -- Fiction; Graphic novels; Science fiction comic books, strips, etc